\(\dfrac{\sqrt{45ab^2}}{\sqrt{20a}}vớia>0,b>0\)
rút gọn các biểu thức:
a,\(6\sqrt{a}+\dfrac{2}{3}\sqrt{\dfrac{a}{4}}-a\sqrt{\dfrac{9}{a}}+\sqrt{7}vớia>0\)
b,\(5a\sqrt{25ab^3}\sqrt{3}\sqrt{12a^3b^3}+9ab\sqrt{9ab}-5b\sqrt{81a^3b}vớia,b>0\)
c,\(\sqrt{\dfrac{a}{b}}+\sqrt{ab}-\dfrac{a}{b}\sqrt{\dfrac{b}{a}}vớia,b>0\)
d,\(11\sqrt{5a}-\sqrt{125a}+\sqrt{20a}-4\sqrt{45a}+9\sqrt{a}vớia>0\)
a: \(=6\sqrt{a}+\dfrac{1}{3}\sqrt{a}-3\sqrt{a}+\sqrt{7}=\dfrac{10}{3}\sqrt{a}+\sqrt{7}\)
b: \(=5a\cdot5b\sqrt{ab}+\sqrt{3}\cdot2\sqrt{3}\cdot ab\sqrt{ab}+9ab\cdot3\sqrt{ab}-5b\cdot9a\sqrt{ab}\)
\(=25ab\sqrt{ab}+12ab\sqrt{ab}+27ab\sqrt{ab}-45ab\sqrt{ab}\)
\(=19ab\sqrt{ab}\)
c: \(=\dfrac{\sqrt{ab}}{b}+\sqrt{ab}-\dfrac{a}{b}\cdot\dfrac{\sqrt{b}}{\sqrt{a}}\)
\(=\sqrt{ab}\left(\dfrac{1}{b}+1\right)-\dfrac{\sqrt{a}}{\sqrt{b}}\)
\(=\sqrt{ab}\)
d: \(=11\sqrt{5a}-5\sqrt{5a}+2\sqrt{5a}-12\sqrt{5a}+9\sqrt{a}\)
\(=-4\sqrt{5a}+9\sqrt{a}\)
a)\(\sqrt{4\left(a-3\right)^2}vớia\ge3\)
b)\(\sqrt{a^2\left(a+1\right)^2}vớia>0\)
c)\(\sqrt{\dfrac{16a^4b^6}{128a^6b^6}}vớia< 0,b\ne0\)
a) \(\sqrt{4\left(a-3\right)^2}=2\left(a-3\right)=2a-6\)
b) \(\sqrt{a^2\left(a+1\right)^2}=a\left(a+1\right)=a^2+a\)
c) \(\sqrt{\dfrac{16a^4b^6}{128a^6b^6}}=\sqrt{\dfrac{1}{8a^2}}=\dfrac{1}{\sqrt{8}\left|a\right|}=\dfrac{1}{-\sqrt{8}a}=\dfrac{-\sqrt{8}}{8a}\)
a: \(\sqrt{4\left(a-3\right)^2}=2\cdot\left(a-3\right)=2a-6\)
b: \(\sqrt{a^2\left(a+1\right)^2}=a\left(a+1\right)=a^2+a\)
c: \(\dfrac{\sqrt{16a^4b^6}}{\sqrt{128a^6b^6}}=\sqrt{\dfrac{16a^4b^6}{128a^6b^6}}=\sqrt{\dfrac{1}{8a^2}}=\sqrt{\dfrac{2}{16a^2}}=-\dfrac{\sqrt{2}}{4a}\)
\(\dfrac{\sqrt{16a^4b^6}}{\sqrt{128a^6b^6}}vớia< 0,b\ne0\)
\(\dfrac{\sqrt{16a^4b^6}}{\sqrt{128a^6b^6}}=\sqrt{\dfrac{16a^4b^6}{128a^6b^6}}=\sqrt{\dfrac{1}{8a^2}}=\sqrt{\dfrac{2}{16a^2}}=-\dfrac{\sqrt{2}}{4a}\)
\(\dfrac{\sqrt{16a^4b^6}}{\sqrt{128a^6b^6}}=\dfrac{4a^2b^3}{8\sqrt{2}a^3b^3}=\dfrac{1}{2\sqrt{2}a}\)
rút gọn các biểu thức sau:
C=\(2\sqrt{a}-\sqrt{9a^3}+a^2\sqrt{\dfrac{4}{a}}+\dfrac{2}{a^2}\sqrt{25a^5}vớia>0\)
\(C=2\sqrt{a}-\sqrt{9a^3}+a^2\sqrt{\dfrac{4}{a}}+\dfrac{2}{a^2}\sqrt{25a^5}\)
\(=2\sqrt{a}-3\sqrt{a}^3+\dfrac{2\left(\sqrt{a}\right)^4}{\sqrt{a}}+\dfrac{10\left(\sqrt{a}\right)^5}{\left(\sqrt{a}\right)^4}\)
\(=2\sqrt{a}-3\sqrt{a}^3+2\sqrt{a}^3+10\sqrt{a}\)
\(=12\sqrt{a}-\sqrt{a}^3\)
Rút gọn các biểu thức sau:
A = \(5\sqrt{a}+6\sqrt{\dfrac{a}{4}}-a\sqrt{\dfrac{4}{a}}+5\sqrt{a}\); \(a>0\)
B = \(3\sqrt{5a}-\sqrt{20a}+4\sqrt{45a}+\sqrt{5a};a\ge0\)
bài 1: rút gọn các biểu thức.
a) \(\dfrac{x\sqrt{x}+y\sqrt{y}}{\sqrt{x}+\sqrt{y}}-(\sqrt{x}-\sqrt{y})^2\)
b) \(\sqrt{\dfrac{x-2\sqrt{x}+1}{x+2\sqrt{x}+1}}(x\ge0)\)
c) \(\dfrac{x-1}{\sqrt{y}-1}\sqrt{\dfrac{(y-2\sqrt{y}+1)^2}{(x-1)^4}}(x\ne1,y\ne1,y>0)\)
bài 2:rút gọn và tính.
a) \(\sqrt{\dfrac{\sqrt{a}-1}{\sqrt{b}+1}:}\sqrt{\dfrac{\sqrt{b}-1}{\sqrt{a}+1}với}a=7,25;b=3,25\)
b) \(\sqrt{15a^2-8a\sqrt{15}+16}vớia=\sqrt{\dfrac{3}{5}}+\sqrt{\dfrac{5}{3}}\)
c) \(\sqrt{10a^2-4a\sqrt{10}+4}vớia=\sqrt{\dfrac{2}{5}}+\sqrt{\dfrac{5}{2}}\)
d) \(\sqrt{a^2+2\sqrt{a^2-1}}-\sqrt{a^2-2\sqrt{a^2-1}}(a=\sqrt{5})\)
bài 3: rút gọn các biểu thức.
a) \(\sqrt{9(x-5)^2}(x\ge5)\)
b) \(\sqrt{x^2.(x-2)^2}(x< 0)\)
c)\(\dfrac{\sqrt{108x^3}}{\sqrt{12x}}(x>0)\)
d)\(\dfrac{\sqrt{13x^4y^6}}{\sqrt{208x^6y^6}}(x< 0:y\ne0)\)
ai giúp mik vs ạ, cảm ơn !
Bài 1:
a. ta có \(\dfrac{x\sqrt{x}+y\sqrt{y}}{\sqrt{x}+\sqrt{y}}-\left(\sqrt{x}-\sqrt{y}\right)^2\)
= \(\dfrac{\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{xy}+y\right)}{\sqrt{x}+\sqrt{y}}-x+2\sqrt{xy}-y\)
= \(x-\sqrt{xy}+y-x+2\sqrt{xy}-y\)
=\(\sqrt{xy}\)
b.ĐK: x ≠ 1
Ta có: A= \(\sqrt{\dfrac{x+2\sqrt{x}+1}{x-2\sqrt{x}+1}}\)=\(\sqrt{\dfrac{\left(\sqrt{x}+1\right)^2}{\left(\sqrt{x}-1\right)^2}}\)=\(\dfrac{\sqrt{x}+1}{\left|\sqrt{x}-1\right|}\)
*Nếu \(\sqrt{x}-1\ge0\Rightarrow\sqrt{x}\ge1\)
⇒ A = \(\dfrac{\sqrt{x}+1}{\sqrt{x}-1}\)
*Nếu \(\sqrt{x}-1< 0\Rightarrow\sqrt{x}< 1\)
⇒ A=\(\dfrac{\sqrt{x}+1}{-\sqrt{x}+1}\)
c.Ta có:
a,\(\sqrt{a^3}-\sqrt{b^3}+\sqrt{a^2.b}-\sqrt{a.b^2}\left(Vớia>0,b>0\right)\)
b,\(x-y+\sqrt{x.y^2}-\sqrt{y^3}\left(Vớix>0,y>0\right)\)
a, \(\sqrt{a^3}\)-\(\sqrt{b^3}\)+\(\sqrt{a^2b}\)-\(\sqrt{ab^2}\)
=(\(\sqrt{a^3}\)-\(\sqrt{b^3}\))+(\(\sqrt{a^2b}\)-\(\sqrt{ab^2}\)). =(\(\sqrt{a}\)-\(\sqrt{b}\))(a+\(\sqrt{ab}\)+b)+\(\sqrt{ab}\)(\(\sqrt{a}\)-\(\sqrt{b}\)). =(\(\sqrt{a}\)-\(\sqrt{b}\))(a+\(\sqrt{ab}\)+b+\(\sqrt{ab}\)). =(\(\sqrt{a}\)-\(\sqrt{b}\))(a+2\(\sqrt{ab}\)+b). =(\(\sqrt{a}\)-\(\sqrt{b}\))(\(\sqrt{a}\)+\(\sqrt{b}\))\(^2\) =(a-b)(\(\sqrt{a}\)+\(\sqrt{b}\))
b, x-y+\(\sqrt{xy^2}\)-y\(^3\) =(x-y)+(\(\sqrt{xy^2}\)-\(\sqrt[3]{y^3}\)). =(\(\sqrt{x}\)-\(\sqrt{y}\))(\(\sqrt{x}\)+\(\sqrt{y}\))+\(\sqrt{y^2}\)(\(\sqrt{ }x\)-\(\sqrt{y}\)). =(\(\sqrt{x}\)-\(\sqrt{y}\))(\(\sqrt{x}\)+\(\sqrt{y}\)+\(\sqrt{y^2}\)). =(\(\sqrt{x}\)-\(\sqrt{y}\))(\(\sqrt{x}\)+\(\sqrt{y}\)+y) (vì y>0).
Câu 48* : Với a 0 thì -2a\(b^2\sqrt{5}\)bằng :
A. \(\sqrt{20a^2b^4}\) ; B. -\(\sqrt{20a^2b^4}\); C. \(\sqrt{10a^2b^4}\) ; D. -\(\sqrt{10a^2b^4}\) .
CM: \(\sqrt{a+b}+\sqrt{a-b}< 2\sqrt{a},vớia,b,c>0\)
Bunyakovsky:
\(\sqrt{a+b}+\sqrt{a-b}\le\sqrt{2.2a}=2\sqrt{a}\)